Kinect-based anthropometric measurements: a comparative analysis of traditional methods in youth female weightlifters - Örücü, S.; Isik, B.; Erdagi, K.; Osmanoglu, U. Ö.; Özbay, E. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The importance of anthropometric measurements for monitoring the physical development of athletes and optimizing training programs is well known. Considering the limitations of traditional methods in terms of accuracy and consistency, the aim of this study is to investigate the potential of Kinect V2 as an alternative.